CANONIC RELATION BASICO-MOTORICAL ABILITIES ON SITUATION SUCCESSFUL CHILDREN IN SMALL FOOTBALL - Izudin Tanović; Jasmin Mehinović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Football appertain to group polystructual sports, which characterize very big number different not standardize motorical abilities and technics which footballplayers execute in variable situations, begin intention or accidently during the game( Elsner,B.1985.).For the difference of the big football,small football or Futsall presents game which is condition with very considerable space and time-limitation which are manifestate with very fast transformation of game from the phase of attack to phase of defence.Dinamic of game, difference of not-standaardize abilities, and application situation individual technic for successful deduction of actions request from player and very big level of psychocondition readiness. The aim of this exploration was to realize the level of influence basico-motorical abilities on situation successful in small football (Futsall game). Exploration is done on the children from the 12-14 years,at the school of small football in SFC "OT of MOSTAR"(OLD TOWN OF MOSTAR) from the Mostar. Take into consideration strature characteristics and magnitude choosen pattern of children, and the target of exploration,processing the results are done with metod canonic-coleration analise. Final results of this exploration are characteristic for exploring strature,but also the same confirmation that exist statisticly very important binded between exploration spaces